2022
DOI: 10.3390/children10010070
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Guided Growth: A Preliminary Study of Its Use in Children

Abstract: Torsional malalignment of the legs is common in children, and those that do not remodel may benefit from surgical correction. Traditionally, this is corrected with an open osteotomy. Guided growth is the gold standard for minimally invasive angular correction and has been investigated for use in torsional deformities. This study presents our preliminary results of rotationally guided growth in the femur and tibia using a novel technique of peripheral flexible tethers. A total of 8 bones in 5 patients were trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…Paley et al ( 14 ) reported achieved rotation in all eight bone segments (five patients) in their study, with an average of 30° in femur and 9.5° in tibia. Seven out of eight segments were corrected with external rotation and one segment was corrected with internal rotation.…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…Paley et al ( 14 ) reported achieved rotation in all eight bone segments (five patients) in their study, with an average of 30° in femur and 9.5° in tibia. Seven out of eight segments were corrected with external rotation and one segment was corrected with internal rotation.…”
Section: Resultsmentioning
confidence: 85%
“…A total of 14 studies (10 preclinical ( 3 , 4 , 9 , 10 , 11 , 12 , 17 , 18 , 19 , 20 ), 3 clinical ( 5 , 13 , 14 ), and 1 review ( 16 )) were included that examined guided growth for rotational deformities.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations